2012
DOI: 10.1364/oe.20.024664
|View full text |Cite
|
Sign up to set email alerts
|

Complete hyperentangled-Bell-state analysis for photon systems assisted by quantum-dot spins in optical microcavities

Abstract: Bell-state analysis (BSA) is essential in quantum communication, but it is impossible to distinguish unambiguously the four Bell states in the polarization degree of freedom (DOF) of two-photon systems with only linear optical elements, except for the case in which the BSA is assisted with hyperentangled states, the simultaneous entanglement in more than one DOF. Here, we propose a scheme to distinguish completely the 16 hyperentangled Bell states in both the polarization and the spatial-mode DOFs of two-photo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
154
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 167 publications
(155 citation statements)
references
References 68 publications
(88 reference statements)
1
154
0
Order By: Relevance
“…Otherwise, setups with more nonlinearities need to be prepared in advance for all possible situations. Second, in our scheme the discrimination of the second DOF is realized without any nonlinear optics while in other schemes the analysis of both DOFs resorts to nonlinearities [44,46]. These two advantages make our scheme time-saving and resourcesaving and thus more useful and practical.…”
Section: Discussion and Summarymentioning
confidence: 98%
See 1 more Smart Citation
“…Otherwise, setups with more nonlinearities need to be prepared in advance for all possible situations. Second, in our scheme the discrimination of the second DOF is realized without any nonlinear optics while in other schemes the analysis of both DOFs resorts to nonlinearities [44,46]. These two advantages make our scheme time-saving and resourcesaving and thus more useful and practical.…”
Section: Discussion and Summarymentioning
confidence: 98%
“…It has been shown that 16 hyperentangled Bell states can be classed into only 7 groups with linear optics [40,41]. Therefore, auxiliary states and assistant tools have to be utilized to accomplish complete state analysis [42][43][44][45][46][47]. In 2010, Sheng et al proposed the first complete HBSA scheme for polarization and spatial-mode hyperentangled states [44].…”
Section: Introductionmentioning
confidence: 99%
“…Based on single electron spin confined in a charged quantum dot inside a microcavity, Hu et al [70] present a scheme to generate photon polarization entanglement. Ren et al [71] proposed a scheme for completing hyperentangled-Bell-state analysis for photon systems. Based on diamond NV centers inside photonic crystal cavities, Ren et al [38] proposed a protocol to implement the hyperentanglement purification of two-photon systems in nonlocal hyperentangled Bell states.…”
Section: Discussion and Summarymentioning
confidence: 99%
“…Hyperentangled states can be used to beat the channel capacity limit of superdense coding with linear optics [23,24], construct hyper-parallel photonic quantum computing [25,26] which can reduces the operation time and the resources consumed in quantum information processing, achieve the high-capacity quantum communication with the complete teleportation and entanglement swapping in two DOFs [27,28]. They can also help to design deterministic entanglement purification protocols [29][30][31][32] which work in a deterministic way, not a probabilistic one, far different from conventional entanglement purifi- * Email address: xihanlicqu@gmail.com cation protocols [33][34][35].…”
Section: Introductionmentioning
confidence: 99%